Dynamics of physiological characteristics and dry matter accumulation under rain-water storage irrigation - Li, Yuanyuan; Shao, Xiaohou; Li, Yanbin; Xiao, Menghua (International Journal of Agricultural and Biological Engineering, 2021)
Photosynthesis is related to dry matter accumulation in aboveground part of rice plant, which is the direct factor of production. This study carried out research on physiological indicators and the relationship between photosynthesis and dry matter accumulation under different water management in paddy field. In general, the photosynthetic and physiological indicators showed the trend of increasing and then decreasing with the growth stage of rice. Experimental results showed that, chlorophyll content and leaf area index of rice leaves showed a quadratic curve positive correlation. Canopy light transmission reached the maximum at heading-flowering stage, and it had quadratic relationship with leaf area index, while it showed extremely positive correlation under rain-water storage irrigation mode. Photosynthetic rate (Pn) and transpiration rate (Tr) had quadratic curve positive correlation with chlorophyll content. The water condition under rain-water storage was favorable for dry matter accumulation in panicle. After multiple regression and main factor analysis, canopy light transmission, light transmission coefficient and Pn were main factors related to dry matter accumulation. The conclusions in this article were helpful for promoting rice yield in practice.Keywords: physiological index, dry matter accumulation, canopy light transmission, regression analysisDOI: 10.25165/j.ijabe.20211403.5771Citation: Li Y Y, Shao X H, Li Y B, Xiao M H. Dynamics of physiological characteristics and dry matter accumulation under rain-water storage irrigation. Int J Agric & Biol Eng, 2021; 14(3): 148–155.